Предмет: Алгебра,
автор: sosnovsckymiti
Решите задачу по шагам
Преобразуйте выражение в многочлен стандартного вида. (2х-3)(х+2)+(х-4)(х+4)
Ответы
Автор ответа:
0
2x^2 + 4x - 3x - 6 + x^2 - 4^2 =
= 2x^2 + x - 6 + x^2 - 16 =
= 3x^2 + x - 22
= 2x^2 + x - 6 + x^2 - 16 =
= 3x^2 + x - 22
Похожие вопросы
Предмет: Биология,
автор: yanazhidkova08
Предмет: Физика,
автор: rreiusajdaskds
Предмет: Окружающий мир,
автор: babadzhanovkamil04
Предмет: Геометрия,
автор: shkredov1
Предмет: Химия,
автор: lepetuhadaniil